2022
DOI: 10.3389/fphar.2022.938239
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of edaravone dexborneol versus edaravone for the treatment of acute ischemic stroke in China: Based on the TASTE study

Abstract: Background and purpose: The TASTE trial indicated that patients with acute ischemic stroke (AIS) using edaravone dexborneol have a significantly higher proportion of 90-day good functional outcomes (mRS 0–1) than those using edaravone. This study compared the cost-effectiveness of the aforementioned interventions in treating AIS in the Chinese setting, aiming to inform treatment decisions in clinical practice.Methods: A model combining a decision tree and a Markov model was developed to assess the cost-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…According to the one-way sensitivity analysis, the top factor with great influence on ICER was the price of ED, followed by the price of NBP, which were different from the findings of cost-effectiveness of ED versus edaravone for the treatment of AIS in China by Shi FH, et al [ 18 ]. The price of ED was lower, the treatment of ED was more cost-effective.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…According to the one-way sensitivity analysis, the top factor with great influence on ICER was the price of ED, followed by the price of NBP, which were different from the findings of cost-effectiveness of ED versus edaravone for the treatment of AIS in China by Shi FH, et al [ 18 ]. The price of ED was lower, the treatment of ED was more cost-effective.…”
Section: Discussionmentioning
confidence: 69%
“…Excess death rate due to stroke was incorporated into the long-term Markov model as the hazard ratio for each mRS health state by using the age-specific death rate multiplied by the hazard ratio for each mRS health state [ 18 ]. The stroke death hazard ratio of mRS 0–1 and mRS 2–5 contracted from the published study by Boudreau et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…[14] Studies have shown that multiple pathways of injury in the ischemic cascade are simultaneous and interact with each other; therefore, combined therapy targeting several pathways of ischemic injury may have advantages over single pathway strategies. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[14] Studies have shown that multiple pathways of injury in the ischemic cascade are simultaneous and interact with each other; therefore, combined therapy targeting several pathways of ischemic injury may have advantages over single pathway strategies. [15] Free radicals are the main cause of ischemic cerebrovascular injury, and the massive production of free radicals after brain tissue injury promotes secondary brain tissue damage. EDA is a potent free radical scavenger.…”
Section: Discussionmentioning
confidence: 99%
“…Given the synergistic effect of edaravone (anti-oxidant) and borneol (anti-in ammation), edaravone dexborneol (EDB), which is composed of edaravone and (+)-borneol at a 4:1 ratio, has been tested as a multitarget agent, and it is satisfactory in protect against brain ischemia. Phase II/III study con rmed the e cacy and safety of EDB in clinical patients with AIS [18][19][20]. However, the immunomodulatory effects of EDB on the central and peripheral immune systems after stroke have not been elucidated elaborately.…”
Section: Introductionmentioning
confidence: 99%